2017
DOI: 10.1089/mdr.2016.0032
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of VIM-4-Producing Pseudomonas aeruginosa and OXA-48-Producing Klebsiella pneumoniae in Northeastern (Annaba, Skikda) Algeria

Abstract: In this study, we report the first detection of P. aeruginosa ST 1076 harboring the bla gene in African countries in two cities (Annaba and Skikda) in northeastern Algeria. Additionally, we report the first detection of bla in K. pneumoniae ST 404 and ST 219 in Algerian cities (Annaba and Skikda).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…Metallo-β-lactamase-producing P. aeruginosa has been extensively reported from different countries in the world [8]. However, data on the prevalent carbapenems resistant phenotypes are limited and poorly investigated in Algeria [9][10][11][12][13]. This work is one among the fewest studies conducted on hospitals in Algeria aiming to project the light on the state of the antibioctic resistance, its level and the main emergent mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Metallo-β-lactamase-producing P. aeruginosa has been extensively reported from different countries in the world [8]. However, data on the prevalent carbapenems resistant phenotypes are limited and poorly investigated in Algeria [9][10][11][12][13]. This work is one among the fewest studies conducted on hospitals in Algeria aiming to project the light on the state of the antibioctic resistance, its level and the main emergent mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…All the strains were positive for phenotypic carbapenemase production as tested by the modified Carba NP (MCNP) test (7). Real-time and standard PCR and sequencing for ␤-lactamase-encoding genes, which were performed using specific primers for the bla CTX-M , bla SHV , bla TEM , bla KPC , bla NDM , bla VIM , bla IMP , and bla OXA-48 genes (8,9), indicated the presence of the bla CTX-M-15 , bla SHV-1 , bla TEM-1D , and bla OXA-48 genes in all isolates. Multilocus sequence typing (MLST) was performed according to the Institute Pasteur scheme (http://bigsdb.web .pasteur.fr/klebsiella/klebsiella.html) and showed that all strains belonged to sequence type 101 (ST101) except for the Kp1 strain, which was assigned to ST985.…”
mentioning
confidence: 99%
“…The modified Hodge test (MHT) and the modified Carba NP (MCNP) test were used to screen for carbapenemase activity (15,16). All strains were screened using real-time PCR for the presence of the following ␤-lactamase-encoding genes: bla KPC , bla NDM , bla VIM , bla IMP , bla OXA-48 , bla CTX-M , bla TEM , and bla SHV (17)(18)(19). Strains positive by real-time PCR were subjected to standard PCR and sequencing (18,20).…”
mentioning
confidence: 99%